Simulation of Wind Power Integration with Modular Multilevel Converter-Based High Voltage Direct Current - Hua Li; Keqilao Meng*; Xiaoyan Li; Yufei Peng (Tehnički Vjesnik, 2022)
The growing demand for large-capacity long distance transmission of wind power has boosted the development of flexible direct current (DC) transmission technology. To facilitate wind power integration, this paper designs a modular multilevel converter (MMC) for steady-state operation, using the parameters of the demonstration DC transmission project of offshore wind power in Sheyang County, eastern China's Jiangsu Province. Relying on the simulation platform of PSCAD/EMTDC, the authors analyzed the proposed control theory, and verified that, under different working conditions (e.g., changing wind speed), the MMC-based high voltage direct current (MMC-HVDC) transmission system can integrate the wind power safely and efficiently. In addition, the authors discussed how to enhance the fault ride-through (FRT), a prominent problem in wind power operation, of the flexible DC system containing wind power, from the perspective of alternating current (AC) fault and DC fault.